1983
DOI: 10.1149/1.2119562
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Pd/Sn and Pd Catalysts for Electroless Plating on Different Substrates Investigated by Means of Rutherford Backscattering Spectroscopy

Abstract: ratio of 12/1 be employed for silox CVD processing. (iii)The deposition rate decrease with increased flow of nitrogen is attributed to two factors, depression of the sil,ane partial pressure and lowering of the wafer surface temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 4 publications
1
15
0
Order By: Relevance
“…80 [5] 60 rM 20 Wave length / nm Since the discovery of giant magnetoresistance in antiferromagnetically coupled Fe/Cr, Co/Cu multilayers, and other metallic multilayer systems,14 interest in magnetic multilayers has been greatly stimulated. Currently the development of new magnetic multilayered nanostructures has attracted considerable attention for potential applicability to magnetoresistive sensor devices.…”
Section: Resultsmentioning
confidence: 99%
“…80 [5] 60 rM 20 Wave length / nm Since the discovery of giant magnetoresistance in antiferromagnetically coupled Fe/Cr, Co/Cu multilayers, and other metallic multilayer systems,14 interest in magnetic multilayers has been greatly stimulated. Currently the development of new magnetic multilayered nanostructures has attracted considerable attention for potential applicability to magnetoresistive sensor devices.…”
Section: Resultsmentioning
confidence: 99%
“…The first is the acid functionalization of CNTs, which was found to be unnecessary. The second is the use of a one-step colloidal Pd–Sn catalyzation approach instead of the two-step stannous chloride and palladium chloride solutions approach for surface activation. ,,,, Accordingly, the processing time was reduced significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work using Pd−Sn colloids has shown that sustained EL metallization requires a threshold surface concentration of >10 15 Pd atoms·cm −2 , a value that exceeds levels for monomeric Pd II /ligand SAM complexes. Consequently, metallization processes using simple ligand SAMs, such as those shown in Scheme , will require binding of Pd-based oligomers or colloids to exceed the threshold.…”
Section: El Metal Depositionmentioning
confidence: 98%